2006
DOI: 10.1111/j.1464-5491.2006.01849.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of circulating hepatocyte growth factor, a new risk marker of carotid atherosclerosis in patients with Type 2 diabetes

Abstract: Serum HGF concentration may be a new marker of atherosclerotic complications in patients with Type 2 DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 24 publications
1
24
0
1
Order By: Relevance
“…Augmented intima-media thickness (IMT) has been demonstrated to be a substitute biomarker for prognosticating CV hazard [72] . In a study by Miyazaki et al [73] , stepwise regression analysis indicated plasma concentrations of ADMA to be remarkably related to carotid IMT.…”
Section: Adma and Carotid Intima-media Thicknessmentioning
confidence: 99%
“…Augmented intima-media thickness (IMT) has been demonstrated to be a substitute biomarker for prognosticating CV hazard [72] . In a study by Miyazaki et al [73] , stepwise regression analysis indicated plasma concentrations of ADMA to be remarkably related to carotid IMT.…”
Section: Adma and Carotid Intima-media Thicknessmentioning
confidence: 99%
“…HGF positively correlated betatrophin in insulin-treated patients. Satani et al (2006) found markedly higher serum HGF in T2DM patients than the normal range [75]. High HGF level is associated with prevalence of T2DM [76] and with depressed cardiovascular autonomic function and IR in T2DM patients [77].…”
Section: Discussionmentioning
confidence: 99%
“…The other biomarkers that have been investigated: urinary 8-hydroxydeoxyguanosine (8-OHdG) (52), osteoprotegerin (53), hepatocyte growth factor (HGF) (54,55), matrix metalloproteinase-9 (MMP-9) (56), cystatin C (57), 1,5 anhydroglucitol (58, 59), neutrophil gelatinase-associated lipocaline (NGAL) (60), , HbA1c, fructosamine, glycated albumin (62).…”
Section: Urinary Proteins (Or Their Fragments) Found Associated With mentioning
confidence: 99%